2014
DOI: 10.1002/ijc.28801
|View full text |Cite
|
Sign up to set email alerts
|

VEGF‐C mediates RhoGDI2‐induced gastric cancer cell metastasis and cisplatin resistance

Abstract: Rho GDP dissociation inhibitor 2 (RhoGDI2) expression is correlated with tumor growth, metastasis and chemoresistance in gastric cancer. However, the mechanisms by which RhoGDI2 promotes tumor cell survival and metastasis remain unclear. In this study, we clearly demonstrate that RhoGDI2 upregulates VEGF-C expression and RhoGDI2 expression is positively correlated with VEGF-C expression in human gastric tumor tissues as well as parental gastric cancer cell lines. VEGF-C depletion suppressed RhoGDI2-induced gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…Consistently, the downstream molecules of AKT, such as c-Myc, and AKT-related anti-apoptotic, metastatic or angiogenic molecules could be efficiently suppressed by KU0060648 treatment. Many studies have shown that these substrates participate in the resistance of certain cancers to chemotherapy [51 - 55]. Taken together, these data revealed that the single agent of KU0060648 or in combination with TMZ in glioma treatment mainly depended on inhibition of AKT signaling.…”
Section: Discussionmentioning
confidence: 82%
“…Consistently, the downstream molecules of AKT, such as c-Myc, and AKT-related anti-apoptotic, metastatic or angiogenic molecules could be efficiently suppressed by KU0060648 treatment. Many studies have shown that these substrates participate in the resistance of certain cancers to chemotherapy [51 - 55]. Taken together, these data revealed that the single agent of KU0060648 or in combination with TMZ in glioma treatment mainly depended on inhibition of AKT signaling.…”
Section: Discussionmentioning
confidence: 82%
“…This evidence suggests that the P5 and P6 peptides not only suppressed VEGFR-3 activation but also subsequently diminished cancer cell migration and invasion. It has been reported that VEGF-C helps cancer cells to survive Taxol treatment via downregulation of mTORC1 function in prostate and pancreatic cancers [ 17 ]; additionally, VEGF-C was shown to enhance cisplatin-resistance through NF-κB activation in gastric cancer [ 18 ]. Moreover, VEGF-C-induced Akt activation has been suggested to promote prostate cancer cell survival [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…A Korea group showed RhoGDI2 confer gastric cancer cells resistance to cisplatin induced apoptosis by several mechanisms. VEGF-C [ 7 ], 14-3-3σ [ 8 ], PLCγ [ 5 ], Bcl-2 [ 6 ] may mediate the effects of RhoGDI2 in drug resistance. However, our previous study showed a different mechanism [ 9 ].…”
Section: Introductionmentioning
confidence: 99%